HUBUNGAN NILAI MATA KULIAH KEWIRAUSAHAAN DENGAN MINAT BERWIRAUSAHA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI STKIP PGRI BANDAR LAMPUNG - Hidayat, Nurdin; Narulita, Sari (Jurnal Elastisitas: Kajian Pendidikan Ekonomi, Ilmu Ekonomi, dan Kewirausahaan, 2019)
The problems in this study are (1) Little interest in students of the STKIP PGRI Bandar Lampung economic study program for entrepreneurship; (2) There are still limited jobs to absorb university graduates in Indonesia; and (3) Number of Educated Unemployment. The purpose of this study was to determine the Relationship Value of Entrepreneurship Subjects with Student Entrepreneurial Interest in Economic Education Study Program STKIP PGRI Bandar Lampung. This research uses quantitative descriptive methods. The population in this study were students of Economic Education Study Program STKIP PGRI Bandar Lampung. Data collection uses a questionnaire and documentation of student grades. Hypothesis testing uses the Product Moment formula. The results showed that there was a relationship between the value of entrepreneurship courses with the interest in entrepreneurship among students of the Economic Education Study Program STKIP PGRI Bandar Lampung